Beyond the Migration Crisis, Deep Values. Where Does Hostility to Immigrants Come from? - Angelucci, Davide; De Sio, Lorenzo; Paparo, Aldo (PARTECIPAZIONE E CONFLITTO, 2021)
Immigration has become a key issue in electoral competition in Italy. Several studies have demonstrated the weight of immigration on voting choices of Italian voters, as well as the importance that this issue has had for the electoral success of certain parties, namely the League. However, it is still unclear why voters are mobilized on this issue and, more generally, what are the underlying factors of individual attitudes towards migrants. In this paper we explore whether and to what extent these attitudes are the result of latent cultural factors, which find their roots in long-standing and deeper value predispositions. We do so, relying on an original survey car-ried out among Italian citizens and making use of the Schwartz conceptualization and measurement of values. A series of regression analyses demonstrate that, besides conditions of objective economic deprivation, prox-imity to migrants, and perception of threat and insecurity, values are the most relevant explanatory factors of attitudes towards immigration. This leads us to conclude that hostile attitudes towards immigration are not the result of a radical transformation of public opinion in Italy, but rather the expression of more general, structur-ally conservative value orientations.